The influence of active and sports games on the functional state and motor activity of first-year university students - Gulxayo Karshiboeva (Science and Education, 2026)
The article examines the problem of improving the functional state and motor activity of university students by means of active and sports games. The aim of the study was to substantiate and experimentally verify the effectiveness of using active and sports games in physical education classes for improving the functional fitness and increasing the daily motor activity of first-year students. The pedagogical experiment lasted one academic semester (16 weeks, two 80-minute sessions per week) and involved 60 first-year male students of Almalyk State Technical Institute, divided into an experimental group (n = 30) and a control group (n = 30). The functional state was assessed by resting heart rate, the Ruffier index, the Harvard step test index, vital lung capacity and the Stange breath-holding test; daily motor activity was measured by pedometry (average number of steps per day). The data were processed using Student’s t-test. By the end of the experiment, the experimental group demonstrated statistically significant improvements in all six indicators, considerably exceeding the changes in the control group, which were statistically insignificant. The results confirm that the systematic use of active and sports games is an effective pedagogical means of improving the functional state and motor activity of university students.